2015
DOI: 10.1186/s12943-015-0473-3
|View full text |Cite
|
Sign up to set email alerts
|

A three-miRNA signature as promising non-invasive diagnostic marker for gastric cancer

Abstract: BackgroundDespite the declining incidence of gastric cancer, mortality rate remains high due to late presentation. We aimed to evaluate the sensitivity of miRNA as a diagnostic marker for gastric cancer in the circulation.MethodsPlasma samples from 3 independent groups comprise 123 gastric cancer patients and 111 healthy controls for miRNA profiling from microarray screening.ResultsMicroarray data showed that 25 miRNAs were upregulated in gastric cancer patients and 6 highly expressed miRNAs (miR-18a, miR-140-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 23 publications
1
68
0
Order By: Relevance
“…Additionally, miR‐627‐5p, which is regulated by small nucleolar RNA host gene 15 (SNHG15), represses the expressions of cyclin dependent kinase 6 (CDK6) and SRY‐box transcription factor 2 (SOX‐2) to suppress the tumorigenesis of GBM . However, the level of miR‐627 is markedly higher in gastric cancer patients compared to healthy controls, indicating an oncogenic role of miR‐627 in gastric cancer . But, the function of miR‐627‐5p has not been investigated in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, miR‐627‐5p, which is regulated by small nucleolar RNA host gene 15 (SNHG15), represses the expressions of cyclin dependent kinase 6 (CDK6) and SRY‐box transcription factor 2 (SOX‐2) to suppress the tumorigenesis of GBM . However, the level of miR‐627 is markedly higher in gastric cancer patients compared to healthy controls, indicating an oncogenic role of miR‐627 in gastric cancer . But, the function of miR‐627‐5p has not been investigated in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…In a study carried out by a group of researchers to analyze miRNA expression profiles across multiple cancers using data sets obtained from The Cancer Genome Atlas (TCGA), miR-629 was found to be upregulated in various cancers, such as bladder, head and neck, lung, kidney, breast and uterine cancer 14. It was also reported that circulating miR-629 is upregulated in lung cancer patients and can potentially be used in diagnosis of lung and gastric cancer 15,16…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that miR-199a-3p plays an important role in suppressing cell proliferation and migration in various tumors, such as prostate cancer [27], colorectal cancer [28], breast cancer [29], glioma [30], osteosarcoma [31] and pancreatic ductal adenocarcinoma [32]. Further studies have demonstrated that miR-199a-3p is a prognosis and diagnosis biomarker in hepatocellular carcinoma [33], gastric cancer [34] and colorectal cancer [35]. In addition, Fornari et al .…”
Section: Discussionmentioning
confidence: 99%